Implementation of Spiritual Services in Mental Problems Conducted by Profession Doctor Program Students Toward Patients at Ibnu Sina Hospital Makassar Year 2023 - I D, Kartika; N F, Khalid; F, Irsandy; I, Royani; A A, Irwan (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: Islamic Discipline of Medicine is one of the advantages in Medical faculty of Universitas Muslim Indonesia which is a special characteristic in our academic. The Islamic Discipline of Medicine is divided into three units. Unit 1 is the basic understanding of Islam, unit 2 is strengthening the professionalism of doctors with Islamic values, unit 3 is strengthening the professionalism of doctors by studying medical sciences from an Islamic perspective. This study, observed the application of unit 2, including Calm the patient, Teaching patients to increase dhikr (Morning and Evening Dhikr, Ask Allah for Forgiveness and other dhikr according to sunnah), and Motivate the patient to keep performing fardhu prayers. The importance of this being done is to create prospective Muslim doctors in accordance with the Vision and Mission of FK UMI so that they can become caliphs on Earth. Methods: This research is a descriptive study using logbook data from Profession Doctor Program Students. The sample technique used is a purpose sampling of medical students which already done their cycle in Interna department in Ibnu Sina Hospital Makassar. Results: From 32 students we found data that’s: 20 student’s makes calm to the patients, 9 students do sometimes, and 3 students didn't do it. About motivating patients to do dhikr: 15 students do it, 7 students sometimes do it, 10 students don't do it and the last motivating to keep performing fardhu prayers: 8 students do it, 9 students sometimes do it, 15 students do not do it. Conclusion: In three aspects of assessment, motivating patients to calm is the best performing compared to motivating patients to do dhikr and motivating patients to keep performing fardhu prayer while there hospitalized. This situation has two probabilities the first is students feel too lazy to motivate the patients or they are hesitant to perform that. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S62